Epilepsy mortality trends in Cuba compared with England and Wales: 1987–2010 - Suárez-Medina, Ramón; Morales-Chacón, Lilia María; Venero-Fernández, Silvia Josefina; Liu, Clarence; Fogarty, Andrew W.; Neligan, Aidan (Elsevier, 2018)
There are limited epilepsy mortality data from developing countries and Latin America in particular. We examined national epilepsy mortality data from Cuba and contrasted them with comparable data from England and Wales. National epilepsy mortality data for Cuba between the years 1987 and 2010 were obtained from the Medical Records and Health Statistics Bureau of the Cuban Public Health Ministry (www.sld.cu/sitios/dne/) with the corresponding mortality data from England and Wales obtained from the UK Office of National Statistics (ONS, www.ons.gov.uk). Indirect standardization with calculation of a standardized mortality ratio (SMR) was used to compare trends. The overall trend was of a slight decrease in mortality rates over the 23 years in Cuba, with higher mortality rates primarily occurring in young people. Annual age-adjusted rates were consistently lower in Cuba than those seen in England and Wales, with the SMR ranging from 0.35 (95% confidence interval (CI): 0.30 to 0.48) in 2007 to 1.00 (95% CI: 0.85 to 1.15) in 1994. Cuban epilepsy mortality rates are consistently lower than those of England and Wales. Reasons for this disparity in mortality rates are not immediately apparent but are likely to be multifactorial.